Formation of Cavity Soliton Using Standing Wave Method - Monga, Vichitra (My University, 2017)
We generated localized patterns in dissipative cavity by standing wave approach. Two dissipative systems are considered, namely, Vertical Cavity Surface Emitting Laser (VCSEL) and VCSEL coupled with Frequency Selective Feedback (FSF) including perturbation gradient. The traveling wave (TW) solutions found by using He‟s Variational Method are considered. The TW solutions are superimposed to form standing wave (SW) patterns inside a cavity for gradient as well as non-gradient systems. Such SW pattern is as steady as a cavity soliton. These standing waves can be referred as cavity solitons if they satisfy three necessary conditions for the formation of soliton, namely, exponential localization, bi-stability and freedom of localization. These standing wave patterns/cavity solitons has many wide ranging applications in all-optical processing, memory devices, etc.
Keywords: Traveling wave solutions; Standing wave; Cavity Soliton; Distributed Bragg reflectors; He's variational method